Evaluation of deformity correction and complications using sublaminar band anchoring in the primary curve of patients with adolescent idiopathic scoliosis - Hemmer, Stefan; Falkenhayn, Moritz von; Trefzer, Raphael; Baumann, Lukas; Pepke, Wojciech (BMC musculoskeletal disorders, 2025)
Background Adolescent idiopathic scoliosis (AIS) is a complex three-dimensional spinal deformity requiring surgical intervention in severe cases. Posterior spinal fusion (PSF) with pedicle screws is the gold standard for correction; however, rigid curves and significant rotational deformities may benefit from adjunctive fixation methods. Sublaminar bands have been proposed to enhance deformity correction while potentially reducing complications. This study aims to evaluate the impact of sublaminar band-assisted constructs versus pedicle screw-only constructs on deformity correction and complication rates in AIS surgery. - Methods A retrospective cohort study was conducted on 165 AIS patients treated with PSF between 2010 and 2024. Patients were divided into two groups: pedicle screws only (n = 124) and pedicle screws with sublaminar bands (n = 41). Demographic, intraoperative, and radiographic data were collected. Propensity score matching was performed to reduce selection bias, and statistical analysis included t-tests, Mann-Whitney U-tests, and Chi-square tests. - Results The mean preoperative Cobb angle was comparable between groups (p > 0.05). While coronal and sagittal correction outcomes were similar, the sublaminar band group showed superior correction in axial rotation (Raimondi angle improvement: 9.8° vs. 5.9°, p = 0.015). No significant differences were observed in overall complication rates or revision surgeries (p > 0.05). Neurological complications were rare in both groups, with intraoperative neuromonitoring contributing to safety. - Conclusion Sublaminar band-assisted constructs provide enhanced axial rotation correction in AIS surgery without increasing complication rates. These findings support the use of sublaminar bands as an effective adjunct to pedicle screws, particularly in cases involving rigid or rotational deformities. Further multicenter prospective studies are warranted to confirm these results.